Time courses of improvement and symptom remission in children treated with atomoxetine for attention-deficit/hyperactivity disorder: analysis of Canadian open-label studies - Turgay Atilla; Gutkin Stephen W; Gibbins Christopher; Maki Ellen; Dickson Ruth A; Weiss Margaret D (Child and Adolescent Psychiatry and Mental Health, 2011)
Abstract Background The relatively short durations of the initial pivotal randomized placebo-controlled trials involving atomoxetine HCl for the treatment of attention-deficit/hyperactivity disorder (ADHD) provided limited insight into the time courses of ADHD core symptom responses to this nonstimulant, selective norepinephrine reuptake inhibitor. The aim of this analysis was to evaluate time courses of treatment responses or remission, as assessed by attainment of prespecified scores on the ADHD Rating Scale-IV-Parent Version: Investigator Administered and Scored (ADHDRS-IV-PI) and the Clinical Global Impressions-ADHD-Severity (CGI-ADHD-S) scales, during up to 1 year of atomoxetine treatment in children with ADHD. Methods Using pooled data from three Canadian open-label studies involving 338 children ages 6-11 years with ADHD who were treated with atomoxetine for 3, 6 and 12 months, and survival analysis methods for interval-censored data, we estimated the time to: 1) improvement and robust improvement defined by ≥25% and ≥40% reductions from baseline ADHDRS-IV-PI total scores, respectively; and 2) remission using two definitions: a final score of ADHDRS-IV-PI ≤18 or a final score of CGI-ADHD-S ≤2. Results The median time to improvement was 3.7 weeks (~1 month), but remission of symptoms did not occur until a median of 14.3 weeks (~3.5 months) using the most stringent CGI-ADHD-S threshold. Probabilities of robust improvement were 47% at or before 4 weeks of treatment; 76% at 12 weeks; 85% at 26 weeks; and 96% at 52 weeks. Probabilities of remission at these corresponding time points were 30%, 59%, 77%, and 85% (using the ADHDRS-IV scale) and 8%, 47%, 67%, and 75% (using the CGI-ADHD-S scale). The change from atomoxetine treatment month 5 to month 12 of -1.01 (1.03) was not statistically significant (p = .33). Conclusions Reductions in core ADHD symptoms during atomoxetine treatment are gradual. Although approximately one-half of study participants showed improvement at 1 month of atomoxetine treatment, remission criteria were not met until about 3 months. Understanding the time course of children's responses to atomoxetine treatment may inform clinical decision making and also influence the durations of trials comparing the effects of this medication with other ADHD treatments. Trial Registrations clinicaltrials.gov: NCT00191633, NCT00216918, NCT00191880.